Comparative Studies on Essential Oil and Phenolic Content with In Vitro Antioxidant, Anticholinesterase, Antimicrobial Activities of Achillea biebersteinii Afan. and A. millefolium subsp. millefolium Afan. L. Growing in Eastern Turkey - TAŞKIN, TURGUT (My University, 2022)
The potential applications of Achillea species in various industries have encouraged the examination of their phytochemical components along with their biological potential. In the present study, phenolic contents and essential oil compositions together with the in vitro biological activities of the aerial parts from Achillea biebersteinii Afan. and Achillea millefolium subsp. millefolium Afan. collected from Turkey were evaluated. Different solvent extracts (n-hexane, chloroform, methanol, water) were prepared and their antimicrobial, anticholinesterase, and antioxidant activities were studied. The LC-MS/MS results revealed the presence of 16 different phenolic compounds, including chlorogenic acid, rutin, quercetin, and luteolin glycosides, in methanolic extracts. According to GC-FID and GC/MS results, the primary components of the oils were identified as 1,8-cineole (32.5%), piperitone (14.4%), and camphor (13.7%) in A. biebersteinii and 1,8-cineole (12.3%) and beta-eudesmol (8.9%) in A. millefolium subsp. millefolium. The infusion and methanolic extracts of both species were found to be rich in their total phenolic content as well as their antioxidant and anticholinesterase activity. In contrast, the n-hexane and chloroform extracts of both species showed strong antimicrobial activity with MIC values ranging from 15 to 2000 mu g/mL. Our findings suggest that the investigated Achillea species could be evaluated as potent natural agents, and further studies into the promising extracts are needed.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Alcaloides; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Structural Biology; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Achillea biebersteinii; Achillea millefolium subsp; millefolium; LC-MS; MS; essential oil; GC-GC; antimicrobial; antioxidant; anticholinesterase; CHEMICAL-COMPOSITION; BIOLOGICAL-ACTIVITIES; PHYTOCHEMICAL ANALYSIS; VOLATILE CONSTITUENTS; EXTRACT; NOBILIS; YARROW; WILD; S.L.; Achillea biebersteinii; Achillea millefolium subsp. millefolium; LC-MS/MS; essential oil; GC-GC/MS; antimicrobial; antioxidant; anticholinesterase